On the Polynomial Asymptotics of Subharmonic Functions of Finite Order and their Mass Distributions - Azarin, V. (Журнал математической физики, анализа, геометрии, 2007)
We obtain the results analogous of those of [5] on the polynomial asymptotics with arbitrary 0 < ρn < ... < ρ1 < ρ, defning multipolynomial terms.